An analysis of smart metering information systems: A psychological model of self-regulated behavioural change. (September 2015) - Nachreiner, Malte; Mack, Birgit; Matthies, Ellen; Tampe-Mai, Karolin
Abstract: Feedback is generally accepted as a suitable intervention technique to foster electricity saving in households. In this domain, smart meters are one promising way to deliver feedback in everyday settings. However, research has shown that feedback by itself is hardly sufficient. Hence, for a more effective design of smart meters, the opportunities which these offer to deliver feedback and to supplement this with other information should be considered. This article describes the specific characteristics of household electricity consumption that should be taken into account. Also, a comprehensive psychological model of self-regulated behaviour change that covers the complete process by which new types of behaviour are chosen and implemented is described in detail and different behavioural stages and components crucial for the design of information strategies are identified. A detailed overview is given of different existing applications and which stages of change these affect. However, as none of these existing smart meters features comprehensive and combined informational strategies that systematically cater to consumers in all stages of behavioural change, it is concluded that further efforts to optimise and evaluate smart meters should be undertaken. A smart meter information system which is designed according to these insights is outlined.